PENGARUH MODEL THINK PAIR SHARE BERBANTUAN VIDEO TERHADAP HASIL BELAJAR SISWA SUBMATERI PENCEMARAN LINGKUNGAN - Saifudin, Muhammad; Ariyati, Eka; Wahyuni, Eko Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aimed of this research was to know the influence of Think Pair Share learning model assisted video media on student learning outcomes in sub material environmental contamination in class VII of SMP Negeri 1 Tujuh Belas. This research was Quasi Eksperimental Design with Nonequivalent Control Group Design. The sample of the study were VIIA class as experimental class and class VIIB as control class. The sampling technique was done by saturated sample technique. Instruments used was in the form of multiple choice test amounted to 20 items. The average post-test result score of experimental class students taught using Think Pair Share learning model with video media was 18.31 which was higher than control class taught using conventional learning at 15.69. Result of analysis of U-Mann Whitney test obtained by Zcount <- Ztable, - 5.14 <-1.96, meaning that there was difference between student learning result taught by using Think Pair Share learning model assisted by video media and conventional learning. The value of effect size was obtained at 1.35 which was in high category and contributes 41.15%. It can be concluded that the learning model of Think Pair Share with the video media has an effect on the result of student learning result on sub material environmental contamination in class VII of SMP Negeri 1 Tujuh Belas.Keywords:Â Think Pair Share, Video Media, Enviromental Contamination